Determining the safety culture in a gun factory in Turkey: A fuzzy approach - (:unkn) unknown (IOS PRESS, 2021)
Safety culture is a very complex phenomenon due to its intangible nature. It is tough to measure and express it with numerical values, as there is no simple indicator to measure it. This paper presents a fuzzy inference system that measures the safety culture. First of all, a safety culture assessment questionnaire is developed by utilizing related literature. The initial questionnaire had 29 items. The questionnaire is applied to 259 employees within the gun manufacturing factory. After making an exploratory factor analysis, the questionnaire is based on five factors with 25 items. The safety culture indicators are defined as; safety follow-up audit reporting, employees' self-awareness, operational safety commitment, management's safety commitment, safety orientedness. Normality, reliability, and correlation analysis are performed. Then a fuzzy model is constructed with five inputs and one output. The inputs are the five factors mentioned above, and the output generated is the safety culture result, which is between 0-1. The presented fuzzy model produces reliable results indicating the safety culture level from the employees' eyes. Beyond exploring the employees' safety culture, the proposed model can easily be understood by the practitioners from various sectors. Furthermore, the model is straightforward to customize for various fields of industry.
Keywords: Fuzzy logic; safety culture; safety culture assessment; safety perception; workplace safety; COMMITMENT; AWARENESS; CLIMATE; MODEL; PERFORMANCE; INDUSTRIES; WORKPLACE; WORKERS